2011
DOI: 10.1007/s11095-011-0452-3
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Hyaluronic Acid Hydrogel Scaffold and PLGA Microspheres for Supporting Survival of Neural Stem Cells

Abstract: Our created HA hydrogel/PLGA microsphere systems have a good potential for controlled delivery of varied biofactors and supporting NSCs for brain repair and implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
80
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(83 citation statements)
references
References 25 publications
3
80
0
Order By: Relevance
“…This was attributed to the fact that released factors might have remained in the hydrogel during the cross-link processing leading to the diffusion through the hydrogel matrix. However, the cumulative amount of bioactive release was reduced to 12% and 13% of total loading as compared to 20-30% in case of microspheres alone which was postulated to be due to the presence of the surrounding HA hydrogel as a delayed or deposited effect on the release profile of the biofactors [17].…”
Section: Hydrogel Scaffold and Microspheres For Supporting Survival Omentioning
confidence: 88%
“…This was attributed to the fact that released factors might have remained in the hydrogel during the cross-link processing leading to the diffusion through the hydrogel matrix. However, the cumulative amount of bioactive release was reduced to 12% and 13% of total loading as compared to 20-30% in case of microspheres alone which was postulated to be due to the presence of the surrounding HA hydrogel as a delayed or deposited effect on the release profile of the biofactors [17].…”
Section: Hydrogel Scaffold and Microspheres For Supporting Survival Omentioning
confidence: 88%
“…Hence, HA hydrogels had the potential to be ideal carriers of BDNF. Recently, our group reported the effect of using PLGA microspheres as carriers for growth factors [112]. VEGF and BDNF were incorporated into PLGA microspheres by a water-in-oil-in-water emulsion technique, and PLGA microspheres were distributed in HA solution before gelation.…”
Section: Modification Of Hyaluronic Acid Hydrogelsmentioning
confidence: 99%
“…are ideal platforms materials for interfacial delivery of NTFs to abnormal tissues in various neural disease treatments; 2) Interfacial surface guidance: processable biopolymers can be fabricated into aligned structures at different scales, including nanofibers [26][27][28] , microfibers [18,19] , microlines [20,21] and micro-tunnels [29,30] , to influence interfacial interactions between neural cells/tissues and surfaces; 3) Interfacial electrical stimulation (ES): ES could be applied on the surface of nerve cells via biocompatible conducting polymers (CPs) platforms to enhance nerve cell proliferation and neurites outgrowth [22] ; 4) Interfacial molecules decoration:…”
mentioning
confidence: 99%
“…recent research revealed that the combinations of these stimulation methods can further improve the interfacial interactions between lesion cells/tissues and polymer based biomaterials, as well as the effects of nerve diseases treatments [29,32] .…”
mentioning
confidence: 99%
See 1 more Smart Citation